Perceptions of Drug Use and Abuse among Adults in Igbo-Eze North Local Government Area of Enugu State, Nigeria: Implications for Social Work Practice - Ngwu, Christopher N.; Osmond, Ogbu Chukwuemeka; Sunday, Abonyi E. (Richtmann Publishing, 2020)
Drug use has not been the problem but rather its abuse and irrespective of the risk thereof, people still abuse them. That is why this study was set out to examine the perceptions of drug use and abuse among adults in Enugu-Ezike in Igbo-Eze North Local Government Area, Enugu State, Nigeria. The study utilized a cross-sectional survey design. The study subjects consisted of 195 respondents (107 males and 88 females) aged 18 years and above. The quantitative data gathered were analyzed with Statistical Package for the Social Sciences (SPSS) using percentages and frequency distribution tables. Chi-square (X2) statistics were used to test the hypotheses The findings showed that 52.3% of the respondents know the meaning of drug use while majority of the respondents were aware of drug abuse. 81.0% of the respondents have negative perception of drug abuse. Also, 54.9% stated that Marijuana is the most abused drug in the study area. Eighty percent (80%) believed that increase in drug abuse increases the rate of crime in the communities. Above thirty-one percent believe that family problems contributed in abusing drugs. The implications of the study to social work practice therefore, is to carry out the public enlightenment, community education, counselling and research on the dangers of drug abuse in Nigeria. The study recommends that the stakeholders in drug use and management should develop appropriate measures to combat the menace of drug abuse that is ravaging our society.